2014
DOI: 10.1111/vru.12142
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stifle Flexion Angle and Scan Plane on Visibility of the Normal Canine Cranial Cruciate Ligament Using Low‐field Magnetic Resonance Imaging

Abstract: Low-field magnetic resonance imaging (MRI) is commonly used to evaluate dogs with suspected cranial cruciate ligament injury; however, effects of stifle positioning and scan plane on visualization of the ligament are incompletely understood. Six stifle joints (one pilot, five test) were collected from dogs that were scheduled for euthanasia due to reasons unrelated to the stifle joint. Each stifle joint was scanned in three angles of flexion (90°, 135°, 145°) and eight scan planes (three dorsal, three axial, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…The MRI coil has a significant impact on the signal-to-noise ratio, and thus on graininess (Mink et al 1993, Banfield andMorrison 2000). Therefore, it is advisable to use a coil well-adjusted to the size of the stifle, which allows for better visibility of the cranial cruciate ligament (Podadera et al 2014). Worthy of mention is a study in human medicine during which the sensitivity of the detection of meniscal tears in the knee with a standard knee coil and a surface coil were compared, and it amounted to 76% and 88%, respectively (Nemec et al 2008).…”
Section: Magnetic Resonance Imaging Of Stifle Jointmentioning
confidence: 99%
See 4 more Smart Citations
“…The MRI coil has a significant impact on the signal-to-noise ratio, and thus on graininess (Mink et al 1993, Banfield andMorrison 2000). Therefore, it is advisable to use a coil well-adjusted to the size of the stifle, which allows for better visibility of the cranial cruciate ligament (Podadera et al 2014). Worthy of mention is a study in human medicine during which the sensitivity of the detection of meniscal tears in the knee with a standard knee coil and a surface coil were compared, and it amounted to 76% and 88%, respectively (Nemec et al 2008).…”
Section: Magnetic Resonance Imaging Of Stifle Jointmentioning
confidence: 99%
“…Among them the following may be mentioned: dorsal recumbency with extended (Baird et al 1999, Martig et al 2006 or flexed hindlimbs (Bottcher et al 2010, Tremolada et al 2014, lateral recumbency with various flexion angles of the stifle (Barrett et al 2009, Podadera et al 2014, or even in sternal recumbency (Harper et al 2011). Pujol et al (2011 reported that lateral recumbency with the stifle flexed at 145 o changed the tension of the cranial cruciate ligament and improved its visibility.…”
Section: Magnetic Resonance Imaging Of Stifle Jointmentioning
confidence: 99%
See 3 more Smart Citations